Buddhism and Confucianism on Homosexuality: The Acceptance and Rejection Based on The Arguments of Religious Texts - Andi Alfian (Al-Adyan: Journal of Religious Studies, 2022)
Recently, the discourse on homosexuality has heated up again in Indonesia. Various responses appear to this phenomenon, some strongly reject it, and some tolerate it. Most of the rejection came from religious circles that used religious arguments. This study explores the core teachings of Buddhism and Confucianism, especially about homosexuality, and compares the two. This study argues that the attitude of Buddhism and Confucianism towards homosexuality is highly dependent on the cultural context in which these religions exist and are practiced. In other words, certain Buddhist/Confucian societies are sometimes more tolerant of homosexual practices than other Buddhist/Confucian societies. That is, the core teachings of religions cannot be merely a measure; culture participates in shaping religious responses to homosexuals. However, it also does not mean that these two religions do not have a unique view on homosexuality. Using the literature study method, this study will focus on exploring the attitudes of these two religions, Buddhism and Confucianism, towards the practice of homosexuality, especially to queering the core teachings of both. The results of this study indicate that in both Buddhism and Confucianism, acceptance and rejection of homosexual practices exist, and almost all use their respective core teachings as arguments. In short, this study contributes to providing an overview of how homosexuality is accepted and rejected in Buddhism and Confucianism. Belakangan ini, diskursus tentang homoseksualitas kembali memanas di Indonesia. Berbagai macam respon yang muncul terhadap fenomena ini, ada kalangan yang menolak dengan keras dan ada pula kalangan yang menoleransi. Sebagian besar penolakan muncul dari kalangan agamawan yang menggunakan dalil agama. Studi ini bertujuan untuk mengekplorasi ajaran inti Buddhism dan Confucianism, terutama tentang homosexuality dan berusaha membandingkan keduanya. Studi ini berargumentasi bahwa sikap Buddhism and Confucianism terhadap homoseksualitas sangat bergantung pada konteks budaya di mana agama-agama tersebut berada dan dipraktikkan. Dengan kata lain, kadang-kadang ada masyarakat Buddhist/Confusian tertentu lebih toleran terhadap praktik homosexual daripada masyarakat Buddhist/Confusian yang lain. Artinya, ajaran inti agama-agama tidak bisa semata-mata menjadi ukuran, budaya turut serta membentuk respon agama terhadap homosexual. Meski demikian, hal itu juga tidak berarti bahwa kedua agama ini tidak punya pandangan khusus terhadap homosexuality. Dengan menggunakan metode studi literatur, studi ini akan fokus menelusuri sikap kedua agama ini, Buddhism and Confucianism, terhadap praktik homoseksualitas terutama dengan tujuan untuk queering ajaran-ajaran inti keduanya. Hasil penelitian ini menunjukkan bahwa baik di Buddhism dan Confucianism, penerimaan dan penolakan terhadap praktik homosexual ada dan nyaris semuanya menggunakan ajaran-ajaran inti sebagai dalil. Singkatnya, kajian ini berkontribusi memberikan gambaran bagaimana penerimaan dan penolakan terhadap homoseksulitas dalam Buddhism and confucianism.